Appropriateness of colonoscopy in a tertiary referral centre - Jabar, Mohd Faisal; Abdul Halim, Muhd Ezman; Alif Gul, Yunus Gul (Elsevier, 2004)
The aim of this study was to determine the appropriateness of colonoscopy in relation to its diagnostic yield, with reference to the guidelines set by the American Society of Gastrointestinal Endoscopy (ASGE). A prospective 90-day audit was performed at Hospital Kuala Lumpur, which is a tertiary referral centre in Malaysia, to examine the appropriateness of colonoscopy by indication. During that time, 257 colonoscopies were performed in 244 patients. The predominant indications for colonoscopy were altered bowel habit (37%) and rectal bleeding (18%). Of the 257 colonoscopies, 216 (84%) were judged to be appropriate by ASGE guidelines. Only 43% of all colonoscopies had positive findings. Positive findings were found in 93% of cases judged appropriate compared with only 7% found in cases deemed inappropriate. There were statistically significant relationships between appropriateness and overall positive yield and between appropriateness and neoplastic findings (p < 0.05). Colonoscopy performed for appropriate indications yield more significant findings, thus, we advocate the use of accepted guidelines to maintain or improve the standard of colonoscopy services.